2010
DOI: 10.1523/jneurosci.0328-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

RIM1α and Interacting Proteins Involved in Presynaptic Plasticity Mediate Prepulse Inhibition and Additional Behaviors Linked to Schizophrenia

Abstract: Several presynaptic proteins involved in neurotransmitter release in the CNS have been implicated in schizophrenia in human clinical genetic studies, in postmortem studies, and in studies of putative animal models of schizophrenia. The presynaptic protein RIM1␣ mediates presynaptic plasticity and cognitive function. We now demonstrate that mice deficient in RIM1␣ exhibit abnormalities in multiple schizophrenia-relevant behavioral tasks including prepulse inhibition, response to psychotomimetic drugs, and socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 93 publications
(120 reference statements)
2
46
0
Order By: Relevance
“…Consistent with this concept, mounting evidence from gene profiling, genetic association, and proteomic analyses indicates that alterations in presynaptic function contribute to the etiology of schizophrenia (Chen et al, 2004;Lee et al, 2005;Behan et al, 2009;Maycox et al, 2009;Faludi and Mirnics, 2011). In addition, several studies have reported alterations in presynaptic function or short-term synaptic plasticity in other mouse models of schizophrenia (Jentsch et al, 2009;Talbot, 2009;Blundell et al, 2010;Earls et al, 2010;Kvajo et al, 2011). Critically, our study extends on these findings by revealing an integrated disease mechanism that links presynaptic dysfunction with corresponding effects on higher-order circuit, network, and cognitive functions.…”
Section: Discussionsupporting
confidence: 76%
“…Consistent with this concept, mounting evidence from gene profiling, genetic association, and proteomic analyses indicates that alterations in presynaptic function contribute to the etiology of schizophrenia (Chen et al, 2004;Lee et al, 2005;Behan et al, 2009;Maycox et al, 2009;Faludi and Mirnics, 2011). In addition, several studies have reported alterations in presynaptic function or short-term synaptic plasticity in other mouse models of schizophrenia (Jentsch et al, 2009;Talbot, 2009;Blundell et al, 2010;Earls et al, 2010;Kvajo et al, 2011). Critically, our study extends on these findings by revealing an integrated disease mechanism that links presynaptic dysfunction with corresponding effects on higher-order circuit, network, and cognitive functions.…”
Section: Discussionsupporting
confidence: 76%
“…The Morris water maze task was conducted essentially as described previously (Powell et al, 2004;Tabuchi et al, 2007). Briefly, a white, circular pool 1.2 m in diameter was filled with water (22 Ϯ 1 C) made opaque with nontoxic, "gothic white" liquid tempera paint, and a circular platform (10 cm in diameter) was submerged ϳ1 cm beneath the surface of the water.…”
Section: Generation Of Shank3mentioning
confidence: 99%
“…Coordination and motor learning were tested using a rotarod essentially as described previously (Powell et al, 2004). Mice were placed on a stationary rotarod (IITC Life Sciences) in a well lit room that was then activated and accelerated from 0 to 45 revolutions/ min over 5 min.…”
Section: Generation Of Shank3mentioning
confidence: 99%
See 2 more Smart Citations